Regional investments in Southern European cities - Theodore Metaxas (SPOUDAI - Journal of Economics and Business, 2011)
The article examines the capacity of four medium-sized cities in Southern Europe, concerning the current situation of their assets (agglomeration economies, urban infrastructures, factors of labor and cost, etc.), the degree of development policies implementation and effectiveness by local authorities and finally the level of local authorities capacity to plan and implement particular policies and partnerships with the private sector in order to shape a favorable and attractive magnitude investments supporting through this way cities development and firms competitiveness. The analysis uses primary data from 310 small and medium sized firms in Southern Europe. At the end, the article provides some important conclusions especially for the studied cities, but also for similar cities in the wider zone of Southern Europe.
Keywords: R11; R12; R15; R58; 330; local characteristics; firm competitiveness; development; policies; research; cities; Southern Europe